REACTION RESULT PREDICTION OF UO2 OXIDATION IN THERMOGRAVIMETRIC USE OF REGRESSION POLYNOMIAL - Sahat Simbolon (Universitas Gadjah Mada, 2005)
Thermogravimetric curve of UO2 oxidation reaction with oxygen from room temperature 25 oC to 425 oC had been depicted in three dimensions. The temperature oxidation reaction of UO2 sample was arranged 5 oC / minute and it was found that increasing of sample weight was 1.3 mg. Uranium dioxide (UO2) had not been reacted yet, reacted UO2, UO3 and U3O8 as the result of oxidation reaction were depicted in three dimensions. The nonlinear relationshps between temperature and time of oxidation reaction of UO2 were simulated in three dimensions using MATLAB Version 5.3 software version.